(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2002)
We investigated the kinetic analysis of human platelet Nitric Oxide Synthase (NOS) activity by the rate of conversion of [³H] arginine to [³H]-citrulline in unstimulated fresh platelets. NOS activity was present in the membrane fraction and cytosol, and was Ca2+- and calmodulin dependent which is a characteristic of endothelial NOS. NOS activity was also dependent of NADPH since the omission of this cofactor induced an important decrease (85,2%) in the enzyme activity. The kinetic varied with protein and arginine concentration but optimum concentrations were found up to 60 minutes, and up to 80 µg of protein at 120 nM of arginine and 0.5 µCi of ³H-arginine. NOS activity in the absence of FAD (flavin adenine dinucleotide), FMN (flavin mononucleotide) and BH4 (tetrahydrobiopterin) was only 2.8% of the activity measured in the presence of these three cofactors. The enzyme activity was completely inhibited by L-NAME (1 mM) (98.1 %) and EGTA (5 mM) (98.8 %). Trifluoperazine (TFP) caused 73.2% inhibition of the enzyme activity at 200 µM and 83.8 % at 500 µM. Under basal conditions, NOS Km for L-arginine was 0.84 ± 0.08 µM and mean Vmax values were 0.122 ± 0.025 pmol.mg-1.min-1. Mean human NOS platelet activity was 0.020 ± 0.010 pmol.mg-1.min-1. Results indicate that the eNOS in human platelet can be evaluated by conversion of [³H]-arginine to [³H]citrulline in an optimized method, which provide reproducible and accurate results with good sensitivity to clinical experiments involving neurological and psychiatric diseases.